New genus of opecoelid trematode from Pristipomoides aquilonaris (Perciformes: Lutjanidae) and its phylogenetic affinity within the family Opecoelidae - Andres, Michael J; Pulis, Eric E; Overstreet, Robin M (Folia parasitologica, 2014)
Bentholebouria colubrosa gen. n. et sp. n. (Digenea: Opecoelidae) is described in the wenchman, Pristipomoides aquilonaris (Goode et Bean), from the eastern Gulf of Mexico, and new combinations are proposed: Bentholebouria blatta (Bray et Justine, 2009) comb. n., Bentholebouria longisaccula (Yamaguti, 1970) comb. n., Bentholebouria rooseveltiae (Yamaguti, 1970) comb. n., and Bentholebouria ulaula (Yamaguti, 1970) comb. n. The new genus is morphologically similar to Neolebouria Gibson, 1976, but with a longer cirrus sac, entire testes, a rounded posterior margin with a cleft, and an apparent restriction to the deepwater snappers. Morphologically, the new species is closest to B. blatta from Pristipomoides argyrogrammicus (Valenciennes) off New Caledonia but can be differentiated by the nature of the internal seminal vesicle (2-6 turns or loops rather than constrictions), a longer internal seminal vesicle (occupying about 65% rather than 50% of the cirrus sac), a cirrus sac that extends further into the hindbody (averaging 136% rather than 103% of the distance from the posterior margin of the ventral sucker to the ovary), and a narrower body (27% rather than 35% mean width as % of body length). A Bayesian inference analysis of partial sequence of the 28S rDNA from Neolebouria lanceolata (Price, 1934), Cainocreadium lintoni (Siddiqi et Cable, 1960), Hamacreadium mutabile Linton, 1910, Opecoeloides fimbriatus (Linton, 1910), Podocotyloides brevis Andres et Overstreet, 2013, the new species, and previously published comparable sequences from 10 opecoelid species revealed two clades. One clade includes deep-sea (> or = 200 m) and freshwater fish opecoelids + Opecoeloides Bremser in Rudolphi, 1819, and a second clade included those opecoelids from shallow-water marine, perciform fishes.
Keywords: Species Specificity; Trematoda; nemoci ryb; Animals; druhová specificita; Phylogeny; zvířata; fylogeneze; Perciformes; Fish Diseases; RNA, Ribosomal, 28S; RNA ribozomální 28S